Kesesuaian ujikaji-ujikaji makmal bagi menilai kebolehrobekan in-situ Batu Pasir dan Syal - Ishak, Mohd. Fakhrurrazi (2005)
Excavation of sedimentary rocks such as sandstone and shale are common scope of work in the field. The main problem exists because using the ordinary mechanical excavation method could not excavate these sedimentary rocks. Therefore, a suitable and appropriate method should be determined. One of the suitable excavation method used for sandstone and shale is ripping. The sedimentary rocks samples are taken from a project site at Bukit Indah, Johor Bahru. Sedimentary rocks like sandstone and shale are categorized under clastic-cemented sedimentary rocks, which contain material and mineral that are nonhomogeneus. It causes nonconformity in rock material and gives variable of strength. The decision to determine the suitable excavation method could be based on selected laboratory experiment. The suitability of selected experiments will be decided on whether they could be used in evaluating the tropical sedimentary rock sample excavatability ability. Refer to laboratory experiment, the materials characteristics could be identified and rocks classification for excavation works using the ripping method could be recognized. Materials characteristics and rocks classification obtained from laboratory experiments shows that sandstone and shale found at the area where samples are suitable for excavation works using ripping method.